Structure and thermal properties of La0.6Sr0.4Co0.2Fe0.8O3d–SDC carbonate composite cathodes for intermediate- to low-temperature solid oxide fuel cells - Abd. Rahman, Hamimah; Muchtar, Andanastuti; Muhamad, Norhamidi; Abdullah, Huda (Elsevier Ltd, 2012)
The structure and thermal properties of La0.6Sr0.4Co0.2Fe0.8O3d–SDC carbonate (LSCF–SDC carbonate) composite cathodes were investigated with respect to the calcination temperatures and the weight content of the samarium-doped ceria (SDC) carbonate electrolyte. The composite cathode powder has been prepared from La0.6Sr0.4Co0.2Fe0.8O3d and SDC carbonate powders using the high-energy ball milling technique in air at room temperature. Different powder mixtures at 30 wt%, 40 wt% and 50 wt% of SDC carbonate were calcined at 750–900 8C. The ﬁndings indicated that the structure and thermal properties of the composite cathodes were responsive to the calcination temperature and the content of SDC carbonate. The absence of any new phases as conﬁrmed via XRD analysis demonstrated the excellent compatibility between the cathode and electrolyte materials. The particle size of the composite cathode powder was 0.3–0.9 mm having a surface area of 4–15 m2 g1. SEM investigation revealed the presence of large particles in the resultant powders resulting from the increased calcination temperature. The composite cathode containing 50 wt% SDC carbonate was found to exhibit the best thermal expansion compatibility with the electrolyte.